REDESIGNING A FUTURISTIC LEARNING MODEL THROUGH THE SCAMPER TECHNIQUE TO DEVELOP 21ST-CENTURY SKILLS IN THE SOCIETY 5.0 ERA - Rasona Pooza Hayati; Fahrur Rozi; Ellianawati Ellianawati; Ahmad Ariadi; Muhammad Abijar Rizaliannor (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to redesign a futuristic learning model through the SCAMPER technique as a framework for developing effective and future-oriented education that responds to the demands of the Society 5.0 era. The study focuses on combining learning models to cultivate students’ critical thinking, creativity, communication, and collaboration skills. Through the substitute, combine, adapt, modify, eliminate, and rearrange stages of SCAMPER, this research integrates Problem-Based Learning as main model, Group Investigation as complement model, and Talking Stick as supporting model into a coherent learning framework. Using a descriptive qualitative method, data were collected through document analysis and literature review, and analyzed following Miles and Huberman’s model comprising data collection, reduction, display, and conclusion drawing. The results show that the redesigned model encourages student-centered learning, active participation, and meaningful interaction between teachers and learners. The integration of collaborative and reflective activities also promotes students’ confidence and communication fluency. Thus, the SCAMPER-based redesign offers a practical reference for educators in constructing innovative, contextual, and adaptive learning models that prepare students to face the complex challenges of the Society 5.0 era.